A preliminary study of the properties of the essential oil from the bulbs of Allium sativum Linn. - Nicolas, William F.; Castillo, Amorita V.; Concepcion. Adoracion B. (Quezon City: College of Pharmacy, University of the Philippines, 1979.)
Essential oil from fresh bulbs of garlic, Allium sativum Linn. (Fam. Liliaceae) was extracted by steam distillation using the Clavenger apparatus, and analyzed for its physical and chemical properties. Chemical analyses done involved thin layer chromatography in various solvent systems, gas chromatography and ultraviolet spectroscopy.
Physical properties of the oil which was yellowish in color and has a characteristic pungent odor has a specific gravity of 1.0525 at 14.5°C and a refractive index of 1.5684 at 25°C. It is very soluble in organic, non-polar solvents such as alcohol, methanol, carbon tetrachloride, ether, etc., and insoluble in water
Although thin layer chromatography showed one major unresolved spot and the uv spectrum of the oil had one maximum absorption at 216 nm, gas chromatography showed that there are three major components which are probably diallyl disulfide (I), diallyl sulfide (II) and an alliin homolog (III). The minor components shown by peaks in gas chromatography may be terpenes, pinene or similar analogs
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, 1979.
Keywords: Garlic